Strategi PT. Matta Indonesia Pada Produk Tegel Kunci dalam Mempertahankan Eksistensi Perusahaan - Yovita Elsa Sekar Dyatmika; Feliza Zubair; Diah Fatma Sjoraida (Jurnal Ilmiah Wahana Pendidikan, 2023)
Society’s enthusiasm towards tiles as one of the flooring cover materials keeps increasing in line with the housing classical concept which is on the rise. For that matter, it creates tight competition among tile manufacturers. This research aims to understand the strategy used by PT. Matta Indonesia, through Tegel Kunci’s product in maintaining the existence of their company in the middle of the global competition. This research is studied using the Competitive Advantage Strategy and Porter’s Five Forces concepts. The research Method Model that is being used is a qualitative research method with a case study approach. By way of in-depth interviews, non-participant observations as well as several documentations, the researcher finds diverse strategies that are used by PT. Matta Indonesia to maintain the existence of their company, one of their strategies is by always implementing the grade or the company’s values that becomes both the reference and the foundation in realizing every company’s activities.